KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 27 PADANG - Zikra, Fadhlan Aulia; Asri, Yasnur; Tamsin, Andria Catri (Universitas Negeri Padang, 2018)
ABSTRACT This article was to (1) describe the level of reading comprehension skills of the text description of the seventh grade students of SMP Negeri 27 Padang (2) to describe the skill level of writing the description text of the seventh grade students of SMP Negri 27 Padang; and (3) to describe the correlational of reading comprehension skills of the description text skill of writing text description of student of class VII of SMP Negeri 27 Padang. Theories used in this research are skill, reading comprehension of description text, writing skill of description, correlation skill reading comprehension text description to skill of writing text description of student class VII SMP Negeri 27 Padang.This research type is quantitative research by using descriptive method. An escriptive method with correlation approach. The population in this study is the students of class VII of SMP Negeri 27 Padang registered in the academic year 2017/2018 which amounted to 210 students. The sample of this study amounted to 40 students. The sampling of this research was done by propotional random sampling technique. The data of this research is score of skill reading comprehension result in the form of objective test and score of skill writing skill in the form of performance test of class VII student of SMP Negeri 27 Padang.Based on the research result. It is also evident in the implementation of learning that shows the interrelationship between one another. Kata kunci: keterampilan membaca pemahaman, keterampilan menulis, teks deskripsi, korelasi